Pelatihan Penulisan Artikel Ilmiah bagi Guru-guru di Sekolah Dasar Negeri 01 Sukamulia - Suryanirmala, Neni; Haeri, Zul (Al-DYAS, 2023)
Writing is not only an essential skill for students but also a crucial aspect in the development of teaching and learning skills for teachers. This abstract discusses the key role of writing in strengthening the abilities of teachers. Based on the analysis of the situation and challenges faced by partners, faculty members as implementers of the Community Service Program (PKM) and professionals from the university will provide a solution to address the difficulties experienced by teachers in writing scientific articles. The solution comes in the form of training in writing scientific papers for elementary school teachers at SDN 01 Sukamulia, Sukamulia District, East Lombok Regency. This training can be described as running with enthusiasm and smoothness due to the significant support in this activity. This activity is also beneficial for teachers to practice writing scientific articles, thereby enhancing the abilities of each teacher at SDN 01 Sukamulia. The results of this activity indicate that elementary school teachers at SDN 01 Sukamulia have gained understanding in writing scientific articles and the methods of publication in accredited or non-accredited national journals.